2023
DOI: 10.1007/s44197-023-00102-7
|View full text |Cite
|
Sign up to set email alerts
|

Spread of SARS-CoV-2 Infection in Adult Populations in Cameroon: A Repeated Cross-Sectional Study Among Blood Donors in the Cities of Yaoundé and Douala

Abstract: Over a period of about 9 months, we conducted three serosurveys in the two major cities of Cameroon to determine the prevalence of SARS-COV-2 antibodies and to identify factors associated with seropositivity in each survey. We conducted three independent cross-sectional serosurveys of adult blood donors at the Central Hospital in Yaoundé (CHY), the Jamot Hospital in Yaoundé (JHY) and at the Laquintinie Hospital in Douala (LHD) who consented in writing to participate. Before blood sampling, a short questionnair… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 33 publications
1
10
0
Order By: Relevance
“…COVID‐19 seroprevalence reached 90% among the 2022 women cohort. This finding is in agreement with others at a similar time in the continent: serosurveys in Cameroon, Gambia, Uganda and South Africa have reported antibody positivity between 87% and 96% during the Omicron wave 16,17,19,50,54 . Although lower, the 76.5% seroprevalence reported in Kenya by Awandu et al greatly surpasses PCR confirmed cases 25 .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…COVID‐19 seroprevalence reached 90% among the 2022 women cohort. This finding is in agreement with others at a similar time in the continent: serosurveys in Cameroon, Gambia, Uganda and South Africa have reported antibody positivity between 87% and 96% during the Omicron wave 16,17,19,50,54 . Although lower, the 76.5% seroprevalence reported in Kenya by Awandu et al greatly surpasses PCR confirmed cases 25 .…”
Section: Discussionsupporting
confidence: 92%
“…This observation has been made by numerous authors, both in individual countries 13,18,21,24,50 and upon meta‐analysis, 47,53 where seroprevalence was not significantly different by these categories. Some authors have suggested that transmission reached such high levels by 2022 that none of the potential risk factors studied could be associated with antibody detection 16 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…among university staff and students (71.3%) in Bandjoun, a kingdom in the West Region of Cameroon [ 37 ], Sandie et al . among blood donors from Douala and Yaoundé (66.3% to 98.4%) [ 38 ], and Diallo et al . among unvaccinated individuals (74.8%) after the Omicron wave [ 39 ].…”
Section: Discussionmentioning
confidence: 99%